O restaurante central como mecanismo de assistência estudantil: um estudo na Universidade Federal do Espírito Santo - Haddad, Mariana Rebello (2013)
This research analyzes the Central Restaurant, of the Federal University of Espírito Santo, and its correlation and impact on student assistance. The research problem was to analyze the socioeconomic performance of Central Restaurant and its contribution to student assistance program at the University concerned. In this sense, the work raised and analyzed the historical, economic and financial data and feedback from students and workers about the service provided by the restaurant in the period of 1992-2012. Methodologically, the study is classified, as to its purposes, as exploratory and descriptive and as to its means, as a case of study, in which the data collection techniques and the evidences were conducted by observation, by interview and documentary research and literature. As a result, in the survey and calculation of expenses, it was identified that the Central restaurant had an expense greater than the sum of the resources from the National Student Assistance Program and the revenue from the sale of tickets. Thus, implementing a cost management in the Central restaurant is recommended since it will allow a view of how the available resources are being allocated, allowing a reduction in expenses and, especially, providing a more efficient management. The survey allowed identifying that the university restaurant is considered an important tool in student assistance, especially for those students who live far from the university or who have low income, because it saves time, money and give access to a meal of quality